Remote Access Facilities in Tribhuvan University Central Library of Nepal - Sharma, Bijaya (Access: An International Journal of Nepal Library Association, 2022)
After the COVID-19 pandemic, Tribhuvan University Central Library (TUCL) has implemented Remote Access Services to provide more effective e-resources services for its users. It has subscribed to Pro Quest database with RemoteXs software. This software is a single portal access system which makes resources available from anywhere, anytime and twenty-four-seven. Through this portal, TUCL has been providing subscribers’ e-resource as well as other free and open access e-resources to all members of TU. The core concern of this paper is to perform a descriptive analysis of the status of the readers of TU who have connected to this software. Necessary information and data required for this study have been collected and analyzed from the records available in the TUCL RemoteXs software. RemoteXs allows a maximum of 30,000 users per year to subscribe to the software but so far only 7501 users of TU constituent unit have connected to it. Data presentation is based on the subscribers of different categories of users like faculty member, students, research scholars and staffs registered from constituent units of Tribhuvan University. This study finds that Tribhuvan University has provided e-resources service with remote access system free of cost for the users of TU constituent campuses and departments but it has not been used as expected.